Plant regeneration of Clitoria ternatea from leaf explants cultured in vitro - Mohamed, N.; Taha, R.M. (2011)
Tissue culture studies of medicinal plant Clitoria ternatea (butterfly pea) was carried out to investigate the regeneration potential of this species in vitro. Leaf explants from aseptic seedling were cultured on Driver and Kuniyuki (DKW) medium together with different concentrations and combinations of hormones napthalene acetic acid (NAA) and benzyl aminopurine (BAP) to achieve regeneration. The economic importance of this species includes use as anticonvulsant, antidepressant, indigestion, constipation, arthritis and eye ailments, as a cover crop and as an ornamental plant in Malaysia. The results obtained showed that BAP induced shoots while NAA induced roots.